Understanding Business Model Innovation from a Practitioner Perspective - Carlos M DaSilva (Journal of Business Models, 2018)
While business model innovations are critical to a company’s long-term survival, they are still poorly understood compared to other kinds of innovations. This paper investigates prior research and reframes business model innovation through a practitioner lens. Reporting on a content analysis of interviews with CEOs of small and medium enterprises in the technology industry, this research investigates their definition of business model innovation. This research intends to contribute to a better understanding of the meaning of business model innovation from a practitioners’ perspective. These findings open new directions for theory development and empirical studies in the business model and innovation management literature.